A historical account of hoogsteen base‐pairs in duplex DNA. Issue 12 (23rd September 2013) - Nikolova, Evgenia N.; Zhou, Huiqing; Gottardo, Federico L.; Alvey, Heidi S.; Kimsey, Isaac J.; Al‐Hashimi, Hashim M.; Breslauer, Kenneth J.; Case, David A.; Walter, Nils G.; Woodson, Sarah A.
ABSTRACT In 1957, a unique pattern of hydrogen bonding between N3 and O4 on uracil and N7 and N6 on adenine was proposed to explain how poly(rU) strands can associate with poly(rA)‐poly(rU) duplexes to form triplexes. Two years later, Karst Hoogsteen visualized such a noncanonical A–T base‐pair through X‐ray analysis of co‐crystals containing 9‐methyladenine and 1‐methylthymine. Subsequent X‐ray analyses of guanine and cytosine derivatives yielded the expected Watson–Crick base‐pairing, but those of adenine and thymine (or uridine) did not yield Watson–Crick base‐pairs, instead favoring "Hoogsteen" base‐pairing. More than two decades ensued without experimental "proof" for A–T Watson–Crick base‐pairs, while Hoogsteen base‐pairs continued to surface in AT‐rich sequences, closing base‐pairs of apical loops, in structures of DNA bound to antibiotics and proteins, damaged and chemically modified DNA, and in polymerases that replicate DNA via Hoogsteen pairing. Recently, NMR studies have shown that base‐pairs in duplex DNA exist as a dynamic equilibrium between Watson–Crick and Hoogsteen forms. There is now little doubt that Hoogsteen base‐pairs exist in significant abundance in genomic DNA, where they can expand the structural and functional versatility of duplex DNA beyond that which can be achieved based only on Watson–Crick base‐pairing. Here, we provide a historical account of the discovery and characterization of Hoogsteen base‐pairs, hoping that this will inform future studies exploring the occurrence and functional importance of these alternative base‐pairs. © 2013 Wiley Periodicals, Inc. Biopolymers 99: 955–968, 2013.